Analisis SWOT Pemasaran Nibras House dalam Meningkatkan Penjualan - Haya Fatimah; Naily El Muna (MANAJEMEN, 2026)
This study explores how Nibras House responds to the rapid growth and intense competition in the Muslim fashion industry by implementing effective marketing strategies and conducting a SWOT analysis. Using a descriptive qualitative approach with data collected through observation, interviews, and documentation, the research evaluates the company’s marketing practices. The findings indicate that Nibras House applies a strong marketing mix, including high-quality products, value-based pricing, strategic locations, active promotions, good customer service, and comfortable store displays. Its main strengths are product quality, brand image, and customer loyalty, while its weaknesses include the perception of high prices and limited innovation at certain times. Opportunities arise from increasing demand and digital marketing, while threats come from competition and changing trends. Overall, these strategies support sustainable sales growth.